Congenital abnormalities: experiences of parents atoshakati intermediate hospital, oshana region, Namibia - Sankombo, Marian; Lukolo, Linda; kanga Kimera, Charles Lukanga (International Journal of Medicine, 2017)
Background: Congenital abnormality (CA) is one among eminent problems in the society that affects the livelihood of the individual, communities and the health sector. It creates uncertainty among family members as they strive to identify ways and means to assist one another in the upbringing of these children born with an anomaly. The ultimate purpose of this study was to describe and explore the experiences of parents of children with congenital abnormalities and to identify the source of support such as parents employs when dealing with the child born with congenital abnormalities. This study was conducted at Intermediate Hospital Oshakati (IHO) in Namibiaâ€˜s Oshana region.Methods: A qualitative, explorative and a contextual study design using a phenomenological approach was utilized throughout this study. In-depth interviews were conducted with twelve â€œpurposefullyâ€ selected participants from the population of parents of children born with congenital abnormalities whose children were either admitted in hospital or brought for follow-up. Data analysis was done using a content analytical method.Results: Data were derived from 12 participants interviewed, comprised of parents of children with reversible and irreversible conditions, long hospitalization, more frequent follow ups and those waiting for surgery. The results were categorized in seven categories, including: 1) A child with congenital abnormalities: the impact of disability; 2) Family relationships; 3) Parenting expectations and practices; 4) Altering oneâ€™s family daily life- treading a new path; 5) Social support; 6) Formal services; 7) Societal and community acceptance.Conclusion: The expectations parents had for a normal child becomes a nightmare when the child they were expecting is born with the disability. Living with such a child can be stressful for parents and other family members. Therefore, exploring and describing the lived experiences of parents of children born with congenital abnormalities is an important in the process of finding ways to assist or support parents to provide proper care for their children.